THE PERFORMANCE OF CIVIL SERVANTS IN LANTORA VILLAGE, POLEWALI DISTRICT, POLEWALI MANDAR REGENCY, WEST SULAWESI PROVINCE - Juharni, Juharni (Indonesian Journal Of Economy Studies, 2023)
This research aims to understand and analyze delivery services in the Lantora Subdistrict. The study employs a qualitative method. Data collection techniques include interviews, questionnaires, observations, and documentation. The research findings indicate that the performance of the Lantora Subdistrict apparatus has been categorized as good. However, the quality of public services in the Lantora Subdistrict is categorized as less satisfactory because it does not yet meet the key indicators of public services, including: simplicity with a score of 41.67%, requirements with a score of 43.75%, clarity with a score of 37.5%, discipline with a score of 35.42%, responsibility with a score of 41.75%, officer's ability with a score of 54.17%, speed with a score of 52.08%, fairness with a score of 43.75%, politeness and friendliness with a score of 60.42%, reasonable fees with a score of 47.92%, certainty of fees with a score of 45.83%, certainty of schedule with a score of 37.5%, environmental comfort with a score of 41.67%, and service security with a score of 43.75%. In conclusion, overall, the quality of public services provided by the Lantora Subdistrict apparatus falls into the good category as indicated. However, the availability of facilities and infrastructure greatly supports community services to ensure that the services provided to the community are effective and meet most of the service indicators in accordance with Minister of State Apparatus Empowerment Decision No. 25 of 2004 Regarding the Community Satisfaction Index.